Persepsi Masyarakat Bermukim di Tepian Sungai Pemuatan Kecamatan Bamaang, Sampit, Kabupaten Kotawaringin Timur - Belly, Rayano; Widjajanti, Retno (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2017)
Population density in urban area of Baamang district, Sampit, Kotawaringin Timur regency led to housing shortage for about 2608 households in that area. Census by Statistics Indonesia in 2010 has shown that recent migrant population in urban area is 7915. This condition led riverbank area as alternative for residential area, which in this case is Pemuatan riverbank. Concentration of population in Pemuatan riverbank has given negative impact such as overdensity which tend to be slum area, and other negative impacts to environment, citizen, and social economic condition. These negative impacts have urged the importance to conduct a research about community perception to settle in Pemuatan riverbank. This research uses positivist approach with quantitative method, which focus on basic theory for the research by statistic analysis.